EXPLORING THE AXIOLOGICAL LEXICON IN CONTRASTIVE LINGUISTICS: CROSS-LANGUAGE PERSPECTIVES ON EVALUATIVE MEANING - Dadabayeva Shirinxon Shuxratovna (Modern American Journals, 2025)
This article presents a multi-dimensional synthesis of five seminal strands in the study of values in language—axiolinguistics, Systemic Functional Linguistics (Appraisal), pragmatics (Politeness & Speech Acts), Critical Discourse Analysis, and cognitive-cultural metaphor theory—and shows how their integration can enrich contrastive-linguistic research and foreign-language teaching. Through a systematic literature review of canonical works (Arutyunova et al., 2007; Halliday, 1978; Brown & Levinson, 1987; Fairclough, 1989; Lakoff & Johnson, 1980; Wierzbicka, 1991, etc.), we identify the key evaluative constructs, analytical units, and pedagogical implications in each framework.